Aportes para la medición de la desigualdad racialista en la Argentina - De Grande, Pablo; Salvia, Agustín (El Colegio de México, 2021)
Abstract: This article presents the results of a skin color measurement undertaken in Argentina in 2017. Attributed and self-perceptive indicators were combined to measure the number of people who do not match the stereotype according to which the Argentine population has historically been described as “white” and descended from Europeans. The results (n=5729) show that, far from being a country comprised exclusively of people of ‘white-European’ origin, 40% of the urban population are not considered part of that group. These results make it possible to estimate the number of people potentially subject to racial prejudice, since they do not recognize themselves -nor were they classified- under the phenotypic category of “white”.